Analysis of Rusip Product Development: Product Profile, Raw Materials, Product Form, Packaging, and Marketing Techniques in Indonesia - Junianto, Junianto; Hidayat, Syamsuddin; Putri, Ismi Nabila; Rizki, Muhammad Novandisya; Diana, Ratna Nurcahaya; Pamuji, Ginanjar; Firdaus, Nasywa Tsabita (Universitas Gadjah Mada, 2025)
Rusip is a traditional fish fermentation product typical of coastal communities in Sumatra, particularly Bangka Belitung. Rusip is made from small fish such as anchovies or bilis that are fermented using salt and palm sugar. This product has the potential to be developed to increase production and competitiveness. This study aims to analyze the development of rusip based on product profile, raw materials, product form, packaging, and marketing techniques. The study was conducted qualitatively using a comparative descriptive analysis method. Data collection was carried out through secondary data observation by reviewing various literature sources related to rusip product development published between 2010 and 2025. The results show that rusip products have undergone developments in raw materials, product form, packaging, and marketing techniques. The raw material, which initially used anchovies, has now been replaced with rucah fish, while fermentation, which previously used spontaneous fermentation bacteria, now uses Lactic Acid Bacteria (LAB). In addition, the paste product form has been developed into a powdered seasoning form, non-vacuum packaging has been developed into vacuum packaging, and marketing techniques, which were initially carried out directly and gradually using WhatsApp and Facebook, have now shifted to e-commerce-based marketing such as Shopee and Instagram.